STRATEGI PEMASARAN DALAM MEMPERTAHANKAN BISNIS UMKM DI TENGAH PANDEMI COVID-19 PRODUK GULA AREN DESA HARIANG KECAMATAN SOBANG KABUPATEN LEBAK BANTEN - Supriadi, Didi; Saleh, Khaerul; Sariyoga, Setiawan (CV. Era Digital Nusantara, 2023)
The purpose of the study is to determine the impact of Covid-19 on the income of SME (Small Midsize Enterprise) Mitra Mandala palm sugar in Hariang Village, Sobang District, Lebak Regency, Banten and to design a marketing strategy for Mitra Mandala SME in dealing with the Covid-19 pandemic. The type of research use is descriptive qualitative research and descriptive quantitative. Types and sources of data using primary data and secondary data. The sampling technique of 6 respondents use interview techniques with research criteria. This research method uses IFE Matrix, EFE Matrix, and Swot Matrix.The analysis results showed that the IFE matrix at Mitra Mandala SME has a total score of 3,151. While the EFE matrix obtained a total score of 2,681. The results of the I-E matrix show that the position of Mitra Mandala SMEs is in cell IV which is in a grow and build condition. The results of the SWOT matrix analysis obtained nine strategies, namely: 1) Providing price discounts/discounts 2) Creating a website to sell sugar palm in the international market, 3) Developing an online sales system to develop the market, 4) Developing sugar palm production technology and sugar palm management, 5) Conducting training for MSME employees of Mitra Mandala, 6) Looking for buyers of sugar palm products outside Indonesia, 7) Identifying sugar palm products entering Mitra Mandala, 8) establishing partner relationships with sugar palm farmers, and 9) developing a warehouse system for storing sugar palm products.